THE EFFECT OF FINANCIAL DISTRESS AND TAX LOAD ON TAX INCENTIVE PARTICIPATION PROGRAMS AFFECTED BY THE COVID-19 PANDEMIC - Trisno Yuwono; Dyah Purwanti (Kesatuan Press, 2022)
During the Covid-19 pandemic, The Government of Indonesia implemented tax incentive programs for taxpayers affected by Covid-19. This study examines several factors that affect companies' participation in tax incentives, while The population data used consists of 139 companies listed on the Indonesia Stock Exchange. The data is secondary data from quarterly and financial reports of the listed firm on the Indonesia Stock Exchange. This study employs logistic regression analysis to examine the motivation to participate in the program. Our findings relieve that financial distress motivates the companies to engage in the tax incentive program. On the other hand, the tax burden positively affects the company's participation in the tax incentive program.